1988
DOI: 10.1111/j.1399-3054.1988.tb00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxycinnamoyl amides in stem explants from flowering and non‐flowering Nicotiana tabacum

Abstract: Flower formation in stem explants was chosen as an experimental system for the study of the function of hydroxycinnamoyl amides (HCAs) in plants. The explants, derived from flowering and non‐flowering Nicotiana tabacum L. var. Xanthi nc., differentiated to two types of callus and afterwards to flower buds. A novel reversed‐phase high performance liquid chromatography method, following sample clean‐up on CM‐Fractogel columns, enabled us to examine HCA concentrations in small tissue samples. Two different groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Stem explants out of the inflorescence of 70 d old tobacco plants were used for in vitro culture. Surface-sterilized internodes were cut into pieces of 1 cm length, cross-sectioned, and placed on solidified nutrition medium as described in Wyss-Benz et al (31).…”
Section: Materials and Methods Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stem explants out of the inflorescence of 70 d old tobacco plants were used for in vitro culture. Surface-sterilized internodes were cut into pieces of 1 cm length, cross-sectioned, and placed on solidified nutrition medium as described in Wyss-Benz et al (31).…”
Section: Materials and Methods Plantsmentioning
confidence: 99%
“…1). In control explants, FP showed the known pattern (31,32) Figure 7. These tendencies were reproducible upon repeating the experiment.…”
Section: Pal Inhibitorsmentioning
confidence: 98%
See 1 more Smart Citation
“…Chemicals, conditions of Nicotiana tabacum L. var. Xanthi nc and in vitro stem culture, extraction of HCAs and HPLC detection were as described in Wyss-Benz et al (1988), unless otherwise indicated.…”
Section: Materials and Methods Generalmentioning
confidence: 99%
“…Some samples were analyzed by the method of Wyss-Benz et al (1988) to determine PAs bound to hydroxycinnamic acids (HCAs).…”
Section: Polyamine Analysismentioning
confidence: 99%